2015
DOI: 10.4236/gep.2015.32006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkali Treatment on Heavy Metals Adsorption Capacity of Sewage Sludge

Abstract: Sewage sludge is the promising raw material for biosorbent preparation. In this work, we evaluated the heavy metals adsorption characteristics of alkali treated sewage sludge (ATSS) by equilibrium studies. The adsorption isotherms were fitted with Langmuir and Freundlich models. Comparing with untreated sewage sludge, the total adsorption capacity (qm) of ATSS (prepared with 0.125 mol/L NaOH) for Cd, Pb, Ni, increased by 0.51, 0.70 and 0.32 mmol/g, respectively. When the NaOH concentration for ATSS preparation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The new band at 2075.03 cm À1 in the case of NL biomass (Figure 6b), the shift at 1743.2 cm À1 (TL biomass) and 1641 cm À1 are due to the C¼O stretching mode of carbonyl groups in esters, alcohol, ethers and carboxylic acids (Jeyasundari et al, 2017). The marked shift at 1562.06 cm À1 (Δ 18 cm À1 ) (TL biomass) was due to the C-N stretching vibration, N-H bending vibration, and the complexation with N-H group (Hu et al, 2015). This shift indicated that acidic groups; carboxyl and hydroxyl, are the chief agents in uptake (El-Gendy et al, 2017).…”
Section: Physical Factors Affecting the Biosorption Of Silver Ion By F Solanimentioning
confidence: 99%
See 1 more Smart Citation
“…The new band at 2075.03 cm À1 in the case of NL biomass (Figure 6b), the shift at 1743.2 cm À1 (TL biomass) and 1641 cm À1 are due to the C¼O stretching mode of carbonyl groups in esters, alcohol, ethers and carboxylic acids (Jeyasundari et al, 2017). The marked shift at 1562.06 cm À1 (Δ 18 cm À1 ) (TL biomass) was due to the C-N stretching vibration, N-H bending vibration, and the complexation with N-H group (Hu et al, 2015). This shift indicated that acidic groups; carboxyl and hydroxyl, are the chief agents in uptake (El-Gendy et al, 2017).…”
Section: Physical Factors Affecting the Biosorption Of Silver Ion By F Solanimentioning
confidence: 99%
“…Alkali treatments increase the electronegativity of the fungal biomass by the ionization of functional groups, thus attract more cations Bux and Kasan (1994); Renitta et al (2019). A decrease in biosorption of Ag(I) in alkali-treated biomass was observed that may be due to the hydrolysis and disintegration of biomass by NaOH solution (Hu et al, 2015). The initial metal ion concentration has a fundamental role as a driving force to cope with the mass transfer resistance between the solid and aqueous phases.…”
Section: Physical Factors Affecting the Biosorption Of Silver Ion By F Solanimentioning
confidence: 99%
“…It is acknowledged that biosorbents can remove metals from sludge by ion exchange and adsorption (Hu et al 2015 ). Both these mechanisms are influenced by biosorbent components and operational conditions with lengthened HRT and SRT enhancing technique removal efficiency (Stoveland and Lester 1980 ; Petrie et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ion exchange removal of heavy metals from sewage sludge is however suggested to yield relatively low efficacy (50–60 %), with both gel and macroporous cation exchange resins demonstrating similar effects (De Villiers et al 1995 ). Adsorption mechanisms, applied to sewage sludge, are influenced by SS and organic compounds which in most instances cause media fouling and plugging, therefore requiring pre-treatment with flocculation, settling and filtration or oil-water separation (Hu et al 2015 ). These limitations alongside the influence of colloids are also responsible for membrane fouling (Fu and Wang 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation